BLUE ECONOMY CONCEPT IN EXTENSION WASTE OF FISH BAUNG INTO FISH OIL IN SUNGAI PAKU VILLAGE KAMPAR KIRI, KAMPAR REGENCY, RIAU PROVINCE - Ilza, Mirna; Ikhsan, Ikhsan; Azhari, Azhari; Buchori, Buchori (INTERNATIONAL JOURNAL OF ECONOMIC, BUSINESS AND APPLICATIONS, 2019)
Service to the public entitled